Malapposed Struts with Cre8, Biomatrix, and Xience Stents Assessed with OCT Immediately after Implantation and at 6-Month Follow-Up: Can the Different Biomechanical Characteristics of the Three Stents Impact on Struts Malapposition? - Cristina Giglioli; Emanuele Cecchi; Chiara Formentini; Marco Chiostri; Niccolò Marchionni; Salvatore Mario Romano (Journal of Interventional Cardiology)
Background. Although the clinical effects of stent malapposition remain controversial, several analyses of stent registries consistently have found that malapposed struts were frequently identified in patients who experienced stent thrombosis. In this study, which is a subanalysis of the previously published CREBX-OCT study, we compared optical coherence tomography (OCT) analysis at the index percutaneous coronary intervention (PCI) and at six-month follow-up in 37 patients randomly assigned to receive, by a single operator, three different second-generation drug-eluting stents (Cre8, Biomatrix, and Xience) aiming to clarify if the malapposition observed at six-month follow-up was persistent or late-acquired. Moreover, we investigated if there were some differences in the behavior of the three different kinds of stents in relation to the struts malapposition. Material and Methods. We analyzed 614 and 599 cross sections and 5514 and 5377 struts at the index PCI and at six-month follow-up, respectively. The qualitative analysis of the plaque composition among the three groups did not show significant differences. Results. The lumen area did not significantly change from the index procedure to the six-month follow-up in the three groups; on the contrary, the number of malapposed struts increased significantly in the Cre8 and Biomatrix groups but not in the Xience group: 0.58 ± 1.51 and 3.29 ± 5.33 (p<0.023) in the Cre8 group, 0.55 ± 1.81 and 1.73 ± 2.28 (p<0.024) in the Biomatrix group, and 0.55 ± 1.5 and 0.25 ± 0.87 (p<0.166) in the Xience group, respectively. Conclusions. Therefore, the malapposition observed at six-month follow-up in our study population could be mainly considered as acquired and attributable to biomechanical reasons due to the structural differences among the three stents. This trial is registered with Clinical Trials.gov Identifier: NCT02850497.